Global warming and adverse pregnancy outcomes – the need for research and intervention - Mahmood, Farid Midhet (International Journal of Health Sciences, 2024)
Global warming poses one of the most significant threats to life on our planet. While its effects are far-reaching, pregnant women and their unborn children are particularly vulnerable. Rising temperatures, extreme weather events, and air pollution associated with climate change directly impact maternal health, leading to adverse outcomes for both mothers and infants. As we grapple with this urgent crisis, it is imperative that we recognize the intersection of climate change and maternal health and take decisive action to protect the well-being of our most vulnerable populations.